Accounting Implications of Smart Farming for Efficiency and Sustainability: A Systematic Review - Sudrajat Martadinata; Arya Zulfikar Akbar; Tri Satriawansyah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study conducts a systematic review to examine the evolving accounting implications of smart farming technologies for enhancing agricultural efficiency and sustainability. Smart farming represents a major shift in agricultural practices through technological innovations that improve productivity and environmental performance. Within this transformation, accounting plays a crucial role in ensuring financial feasibility, sustainability integration, and informed decision-making. The importance of this review lies in its ability to consolidate diverse methodological insights, clarify how accounting practices must adapt, identify gaps in the current literature, and illuminate the strategic implications of technological adoption for investment and risk assessment.Despite its potential, smart farming presents a significant research gap: widespread adoption often overlooks substantial initial capital requirements and ongoing operational costs that traditional accounting struggles to fully capture. Moreover, smart farming relies heavily on data, raising complex challenges concerning data privacy, ownership, security, and the valuation of data as an intangible asset. Environmental and social trade-offs further complicate existing accounting frameworks, which may be ill-equipped to integrate such multidimensional impacts.This review aims to synthesize existing scholarship to understand these emerging accounting implications. It specifically examines how smart farming affects traditional accounting practices, including shifts in cost structures, asset valuation, risk management, and sustainability reporting, while highlighting the opportunities and challenges introduced by new technologies. The methodology consists of a systematic literature search in Scopus using keywords related to “traditional,” “smart farming,” “accounting implications,” “efficiency,” and “sustainability.” Filters were applied for publication years (2015–2025), subject areas (Agriculture and Biological Sciences, Environmental Science, Business, Management and Accounting), and document type (Article). After abstract screening, 96 articles were selected for full-text review.Key findings indicate that smart farming redefines agricultural accounting, requiring broader integration of environmental, social, and governance dimensions. Adoption demands granular cost tracking, updated reporting frameworks, and robust risk management approaches. Future research should refine accounting models, create new sustainability metrics, employ interdisciplinary methods, and conduct regional comparative studies to support context-specific best practices.